Detection of the Insonification Area of a Multibeam Echo-Sounder Using a Front Propagation - Debese, N.; Bisquay, H. (The International Hydrographic Review, 2015)
For the execution of its bathymetric surveys, the French Hydrographic and Oceanographic Service of the Navy (SHOM) has been operating three MultiBeam Echo-Sounders (MBES) for three years. These systems carry out simultaneous depth measurements along the transversal axis of the ship, decreasing the time for collecting the data. Planning, managing as well as running a bathymetric campaign rely on a synthetic representation of the area observed by the Echo-Sounder. Representations previously used were only based on an approximation of the covered area obtained by making the assumption that the insonification area of each beam is fixed. This paper proposes an alternative method for building an insonification area based on a standard operation of mathematical morphology: dilation. The originality of our approach lies in its implementation. A reformulation of the dilation in terms of constant fronts propagation to perform a fixed covered area allows optimization of both time and precision (Euclidean distance). This also gives rises to an efficient implementation of an adaptive dilation. This results in a more realistic and accurate representation of the covered area in an acceptable processing time. Used during the planning of the campaign, it allows the simulation of a covered area from a rough Digital Elevation Model and the Echo-Sounder parameters.